The Influence of Education on Increasing Women's Empowerment for Early Detection of Pregnancy Complications in Sigi Regency - Ni Komang Yuni Rahyani; Siti Hadijah Batjo; Nurmiaty Nurmiaty; Hadina Hadina; Roy Rillera Marzo (Buletin Penelitian Kesehatan, 2025)
Background: Women’s empowerment plays a critical role in improving maternal and family health, particularly through timely recognition of pregnancy danger signs and informed decision-making. Educational interventions are expected to enhance women’s knowledge, attitudes, skills, and empowerment related to the early detection of pregnancy complications. This study examined the effect of education on women’s empowerment and behavioral outcomes regarding pregnancy danger signs among third-trimester pregnant women in Sigi Regency, Indonesia. Methods: A quantitative quasi-experimental study with a pretest–posttest design without a control group was conducted from June to October 2023. Eighty-five pregnant women with gestational age >28 weeks were recruited from four community health centers. Participants received structured education using a pocket book on danger signs during pregnancy, childbirth, and the postpartum period. Data were collected using a validated self-reported questionnaire. Paired t-tests were used for data analysis. Results: Mean scores for knowledge (8.74 to 9.35), attitudes (19.07 to 21.46), and skills (20.69 to 25.91) regarding pregnancy danger signs increased significantly after the intervention (p<0.05). Although the empowerment score increased (14.65 to 16.27), the difference was not statistically significant (p>0.05). Conclusion: Educational intervention effectively improved pregnant women’s knowledge, attitudes, and skills related to pregnancy danger signs, but was insufficient to significantly enhance women’s empowerment. Comprehensive, family-centered strategies are needed to strengthen women’s autonomy in maternal health decision-making.